2021
DOI: 10.3390/medicina57121365
|View full text |Cite
|
Sign up to set email alerts
|

Permissible Outcomes of Lobe-Specific Lymph Node Dissection for Elevated Carcinoembryonic Antigen in Non-Small Cell Lung Cancer

Abstract: Background and Objectives: Lobe-specific nodal dissection (L-SND) is currently acceptable for the dissection of early-stage non-small cell lung cancer (NSCLC) but not for cancers of more advanced clinical stages. We aimed to assess the efficacy of L-SND, compared to systemic nodal dissection (SND). Materials and Methods: We retrospectively collected the clinical data of patients with carcinoembryonic antigen (CEA) abnormality who underwent complete resection of NSCLC via lobectomy or more in addition to either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Four studies had additional inclusion criteria, such as radiologic 16 , 23 , 24 or laboratory variables. 21 Most studies excluded patients who underwent neoadjuvant treatment and sublobar resection. Only five studies revealed explicitly precluded main lesions in the right middle lobe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies had additional inclusion criteria, such as radiologic 16 , 23 , 24 or laboratory variables. 21 Most studies excluded patients who underwent neoadjuvant treatment and sublobar resection. Only five studies revealed explicitly precluded main lesions in the right middle lobe.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of surgical procedures, the surgical extent has been modified because LS-LND was firstly suggested by Okada et al. 9 Though there was some variability in the lymph nodes that should be removed, six recent studies 10 , 16 , 21 , 23 , 24 , 25 had the same description, which represented an improved and well-established current practice ( Supplementary Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Satoh et al ( 22 ) reported that male, smoking, diabetes mellitus, subcarinal lymphadenectomy, and pulmonary complications were risk factors for postoperative ischemic bronchitis. Considering the risk of ischemic bronchitis and distribution of lymph node metastasis ( 15 , 16 , 23 ), lobe-specific selective lymphadenectomy has been our standard procedure for primary lung cancer, which could have possibly preserved blood flow at the bronchial stump, thereby reducing the incidence of BPF. In this study, history of gastric cancer surgery was significantly associated with the development of BPF.…”
Section: Discussionmentioning
confidence: 99%
“…The standard procedure for lung cancer in the study period was lobectomy with lobe-specific selective lymph node dissection ( 3 , 15 , 16 ), and subcarinal lymphadenectomy was omitted for lung cancer in right upper lobe and left upper division segment. In right lower lobe lung cancer, upper mediastinal lymph node dissection was omitted unless metastasis was found in the hilar and subcarinal lymph nodes.…”
Section: Methodsmentioning
confidence: 99%